Impact Assessment of Integrated Community Development Project in Mid Western Hill Region, Nepal - Pokhrel, Hari Prasad (Economic Journal of Nepal, 2015)
This paper attempts to analyze the impacts and effectiveness of the Integrated community development project (ICDP) in Mid Western hilly region, which was supported by Action Aid Nepal (AAN) and implemented by Jajorkot Permaculture Program (JPP) by using right based approach with special focus on natural resource management, food rights and child rights. Qualitative techniques were used to point out the overall outcome of the project. Evaluation study has found positive impacts in terms of benefits to project participants, achievement of outputs and success in reaching the targeted goals. The project has made efficient use of its inputs and has established itself as an innovative organization to implement the integrated rural resource base community development in the remote region of Nepal. However, some lacking have been observed in terms of ensuring people's participation for the conservation and management of natural resources like land water and forest. Government has to promote participatory approach to community development and to appreciate good activities done by international and national organizations on rural resource management and eco-friendly development which are replicable in other such geographical area where rural poverty creates serious threats to the environment.Economic Journal of NepalVol. 34, No. 2, Issue no. 134, 2011